Navigating the Nexus: Acute Kidney Injury in Acute Stroke – A Prospective Cohort Study - Sameer Arora; Arpit Agrawal; Venugopalan Y. Vishnu; Mamta B. Singh; Vinay Goyal; Padma M. V. Srivastava (Annals of Indian Academy of Neurology, 2024)
Background: Acute kidney injury (AKI) is prevalent in patients with acute stroke. Although AKI is linked to poor clinical outcomes, data about its incidence and effect on stroke outcomes is limited. Methods: This was a prospective observational study carried out at a single tertiary care center that analyzed the data of 204 consecutive subjects with acute ischemic stroke and intracerebral hemorrhage. Considering serum creatinine at admission as the baseline, AKI was deﬁned as a rise in serum creatinine value of 0.3 mg/dl over 48 h or a percentage increase of at least 50% from baseline over 7 days during hospitalization. The primary outcome was to measure the prevalence of AKI in patients with acute stroke. Secondary outcome measures were all-cause mortality, duration of hospital stay, need for dialysis, and comparison of outcomes in ischemic and hemorrhagic stroke. For both the stroke subtypes, we employed a multivariate logistic regression model, with AKI and hospital mortality being the outcomes. Covariates included gender, age, ventilatory requirement, duration of hospital stay, and National Institutes of Health Stroke Scale score at admission. Results: There were 144 cases of ischemic stroke with 12 deaths (8.3%) and 60 cases of intracranial hemorrhage (ICH) with 22 deaths (36.7%). The mean age was 55 years, 72.6% were males, and AKI complicated 34% of ischemic stroke and 66.7% of ICH hospitalizations. AKI was linked to increased hospital mortality from ischemic stroke (odds ratio [OR] 27.21, 95% CI 3.39–218.13) and hemorrhagic stroke (OR 5.12, 95% CI 1.29–20.28) in multivariate analysis stratiﬁed by stroke type. Conclusions: AKI complicates stroke frequently and increases hospital mortality. Additional studies are required to assess if the association is causal and if remedies to prevent AKI would decrease mortality.